Characterization and comparison between lithium iron p hosphate and lithium-polymers batteries. (November 2016) - Sergi, F.; Arista, A.; Agnello, G.; Ferraro, M.; Andaloro, L.; Antonucci, V.
Highlights: Lithium polymer and lithium iron phosphate main features. Thermal behaviour of, LiFePO4 and Li-Poly cells charging and discharging. Pulse test. OCV Test and evaluation of internal resistance. Stationary and automotive test. Abstract: Electrochemical storage systems are increasingly employed in stationary and automotive applications. The lithium-ion technology nowadays shows the best features and future development prospects. Nevertheless, lithium-ion chemistries are a lot and there is the need to know in deep their behaviour in relation to the final applications. Among the most used Lithium technologies, the CNR-ITAE has selected two different Lithium technologies: Lithium-Iron-Phosphate (LiFePO4 ) and Lithium-Polymers to be tested and compared. Indeed, several electrical vehicles developers and electrical network operators are choosing these specific chemistries for their safety, relatively low cost and flexibility in creating customized battery pack. This paper reports the results of several tests carried out in order to investigate the features of each battery technology for stationary and automotive applications. In particular, the capacity reduction (Peukert effect) and the cell efficiency were analysed. Furthermore, tests showed the different relax time effect and the dynamic behaviour of cells subjected to different load profiles compliant with IEC (International Electrotechnical Commission) tests procedures. A final analysis was carried out comparing the main performance indicators (Capacity, Amperometric and Energetic Efficiency, working temperatures, etc.).